A systematic review of worldwide epidemiology of psoriasis. (30th August 2016) - Michalek, I.M.; Loring, B.; John, S.M.
Abstract: To inform the WHO Global report on psoriasis, a new comprehensive worldwide systematic review of the epidemiology of psoriasis was undertaken. The aim of this study was to systematically review the worldwide literature regarding the epidemiology of psoriasis, including prevalence and incidence, in adults and in children. A search of 15 electronic medical databases was performed. Using a rigorous systematic protocol, eligible articles were analysed. No language, regional or temporal restrictions were applied. A total of 76 study observations met all eligibility criteria and were included in the systematic review. The estimates of the prevalence of psoriasis in adults ranged from 0.51% to 11.43%, and in children from 0% to 1.37%. Psoriasis is a common disease, occurring more frequently with advancing age. Limited data on the epidemiology of psoriasis are available. The available prevalence data come from only 20 countries, meaning there are huge geographic gaps in knowledge, especially from low‐ and middle‐income settings.